Parkinsonism associated with prolonged unresponsive wakefulness syndrome after blunt head injury: a clinico-pathological study - Jellinger, Kurt A. (Free Neuropathology, 2025)
Objective: Survival after traumatic brain injury (TBI) and posttraumatic parkinsonian-like symptoms is increasing, in particular in those patients developing during disease course an unresponsive wakefulness syndrome (UWS) previously termed persistent vegetative state. Material & methods: 100 patients with disorders of consciousness after a blunt TBI ranging from deep coma to defective states / minimal cognitive state survived between 12 and 900 days. 15 patients developed parkinsonian symptoms, which were correlated with their neuropathological changes. Results: The patients, surviving either UWS recovery (n = 10) or defective minimally conscious state (MCS) (n = 5), clinically presented with severe (n = 7), moderate (n = 5), or mild (n = 3) parkinsonian symptoms mainly comprising symmetrical rigidity, amimia, hypo- / akinesia and convergence disorder, which in six patients were associated with unilateral or bilateral resting tremor. Following levodopa treatment, 11 patients showed mild to moderate improvement and four patients almost complete improvement of UWS, parkinsonism or both. Neuropathology revealed in most cases supratentorial traumatic lesions such as contusions, cerebral hemorrhages and diffuse white matter lesions. In addition to lesions in the basal ganglia and hippocampus, all cases displayed older lesions in the dorsolateral or lateral parts of the pons and in lower midbrain with various involvement of substantia nigra. The periaqueductal gray and upper midbrain tegmentum were however preserved. The pattern of brainstem lesions correlated with the sequelae of transtentorial shifting due to increased intracranial pressure. Conclusions: These and other rare observations following blunt TBI confirm the importance of the pattern of secondary brainstem lesions for the development and prognosis of UWS and rare parkinson-like symptoms.